Pendekatan simulasi dalam mengoptimalkan pengoperasian gerbang tol - Sediono, Wahju; Handoko, Dwi (2005)
Despite many existing toll-roads there are always traffic jams detected and reported at several toll-road’s points. Previous simulations have shown that the number of operating toll-gates and the processing time at the toll-gate play an important role in controlling the traffic flow. If the number of the operating toll-gates are much lesser than the number of vehicles passing through the toll-gates then the traffic flow will be severely influenced. Another factor affecting the traffic flow is the vehicle arrival’s rate that is dynamically changing over time. In this paper we investigate some strategies of the toll-gate’s operation dependently on the vehicle arrival’s rate. Based on a simple queuing system we can demonstrate and simulate time-varying arrival’s rate of vehicles on the toll-road. Some simulation results related to these strategies will be discussed in this paper. Accordingly a suitable open-close strategy of the operating toll-gates can be optimized to control the traffic flow on the toll-road.